Instrumentos para avaliar o uso da prática baseada em evidências: o teste modificado de Fresno para avaliação de competências e habilidades pelo profissional fisioterapeuta - Silva, Anderson Martins da (2021)
Introduction: The Modified Fresno Test was developed to assess competencies and skills for Evidence-Based Practice in Physiotherapy professionals and students. Objectives: To describe the exploratory and confirmatory factor structure of the Modified Fresno Test adapted for Brazilian Portuguese and to analyze the statistical feasibility for the elaboration of a short version of the instrument; evaluate, summarize and describe the instruments that assess the use of Evidence-Based Practice in health professionals, currently available; test the measurement properties of the Modified Fresno Test: short version for physical therapists in the Brazilian version, through internal consistency, construct validity, intra- and inter-evaluator reliability and instrument agreement, and; to evaluate the responsiveness of the short version of the Modified Fresno Test: short version.Method: For construct validity, Exploratory Factor Analysis (EFA) was performed using the principal components method, followed by Confirmatory Factor Analysis (CFA). The total score of the 114 questionnaires in the test and retest was evaluated, totaling 228 observations. To investigate the factorability of the instrument, the Kaiser-Meyer-Olkin test and the Bartlet sphericity test were used. To describe the instruments that assess the use of EBP in health professionals, a systematic search was carried out in the following databases: PUBMED, EMBASE, CINAHL and ERIC. Eligibility criteria were used for the studies. The assessment of the methodological quality of eligible studies was analyzed according to the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) checklist. Other characteristics of the instruments identified were also extracted, such as sample size, target audience, year of publication and method of application of the instrument. For the statistical tests of reliability and agreement, the comparison of the score per question and the total score of the test was considered, in a test and retest design for each evaluator (intra-evaluator reliability) and between evaluators for the score obtained in the test. retest (inter-rater reliability) in a sample of 133 physical therapists. Reliability was assessed by analyzing internal consistency using Cronbach's alpha coefficient. To assess agreement, the Standard Error of Measurement (SEM) was used. Responsiveness was analyzed using the method based on data distribution (distribution-based methods), using the effect size (ET). For the analysis of construct validity, Confirmatory Factor Analysis (CFA) was performed using the principal components method. For the analysis of responsiveness, the test was applied pre and post-educational intervention in 35 students of the last year of training in Physiotherapy. For analysis of the sample distribution, the normality test was used. The t test compared the sum total of the participants' responses, the domains of the instrument and the anchor question before and after the intervention. Responsiveness was analyzed using methods based on data distribution by effect size and methods based on anchors, considering the global assessment of change and the participants' level of EBP knowledge.Result: For the factor analysis of the instrument, the internal consistency indicated a value of 0.81 for the instrument's questions. The Kaiser-Meyer-Olkin test showed acceptable values ​​(KMO=0.80). Bartlett's sphericity test indicated that the correlations were sufficient for the analysis. The analysis showed the presence of 3 factors (eigenvalues ​​> 1) related to the 13 items of the instrument, which explains 60.94% of the total variance. In CFA, the two models tested did not provide adequate adjustments. However, the second model that tested a three-factor structure provided a better fit to the data. The systematic review study identified 6,429 studies and only 92 were considered eligible for data analysis. 46 instruments were identified, 40 of which were new in relation to the previous study. Of these, most were developed for nursing professionals and physical therapists. The investigators performed at least 1 type of validity test on 73% of the instruments evaluated in the study. Reliability was tested in 90% of the instruments, through internal consistency. Responsiveness was tested on less than half of the instruments (30%). The Fresno Test remains the most appropriate instrument to assess the use of EBP in healthcare professionals. In the test of measurement properties of the Modified Fresno Test: short version, the inter and intra-evaluator reliability were, respectively: ICC= 0.93 (95% CI 0.91 to 0.95); evaluator 1 - CCI=0.95 (95% CI 0.94 to 0.97); evaluator 2 - ICC= 0.98 (95% CI 0.98 to 0.99) for the total sum of the instrument's questions. The agreement by the EPM was 10.38 points for the inter-evaluator evaluation, 8.72 points for evaluator 1 and 4.52 points for the evaluator 2. The α coefficients calculated for the corrected item-total presented values ​​greater than 0.40. In CFA, “model 2” presented acceptable GFI and CFI indexes (≥ 0.90). Thus, the short version model tested provided a better fit to the data. For the total sum of responses, the glass Delta presented effect size values ​​of 0.13 points and classified as “very small”. In the responsiveness test, there was an increase in scores between pre- and post-intervention, indicating a progressive improvement in the participants' competencies and skills for EBP. The glass Delta that evaluated responsiveness presented effect size values ​​classified as “large” and “very large”, for the sum of responses of all variables evaluated post-operatively educational intervention.Conclusion: The Modified Fresno Test adapted for Brazilian Portuguese showed satisfactory factorial validity and good internal consistency. The study proposes the short version of the test and suggests new studies to improve the instrument. A systematic review of the instruments used to assess the use of EBP identified 92 studies and 46 instruments, 40 of which were new in relation to the previous study. Most are consistent and reliable for measuring the use of EBP in healthcare professionals. The checklist (COSMIN) classified 7 (seven) instruments as being suitable for use in the target audience. Furthermore, the Modified Fresno Test: short version showed excellent reliability and internal consistency. The results of the Confirmatory Factor Analysis showed that the fit indices of the short version model. These results allow us to state that the short version of the test is a very suitable alternative to comprehensively assess EBP in physiotherapy professionals and students. Finally, the Modified Fresno Test: short version was sensitive to identify changes in knowledge regarding EBP in Physical Therapy students. This makes it possible to use it to assess the change in knowledge, skills and attitudes towards EBP within a training curriculum in the population of interest.